FRA18C: a new aphidicolin-inducible fragile site on chromosome 18q22, possibly associated with in vivo chromosome breakage. Issue 5 (2nd May 2007) - Debacker, Kim; Winnepenninckx, Birgitta; Ben-Porat, Neta; FitzPatrick, David; Van Luijk, Rob; Scheers, Stefaan; Kerem, Batsheva; Frank Kooy, R
Abstract : Fragile sites are specific genomic loci that form gaps, constrictions and breaks on chromosomes exposed to replication stress conditions. In the father of a patient with Beckwith-Wiedemann syndrome and a pure truncation of 18q22-qter, a new aphidicolin-sensitive fragile site on chromosome 18q22.2 (FRA18C) is described. The region in 18q22 appears highly enriched in flexibility islands previously found to be the characteristic of common fragile site regions. The breakpoint was cloned in this patient. The break disrupts the DOK6 gene and was immediately followed by a repetitive telomere motif, (TTAGGG)n . Using fluorescent in situ hybridisation, the breakpoint in the daughter was found to coincide with the fragile site in the father. The breakpoint region was highly enriched in AT-rich sequences. It is the first report of an aphidicolin-sensitive fragile site that coincides with an in vivo chromosome truncation in the progeny.